The effectiveness of additional medical management of patients in the early stages after reconstructive interventions on the auxiliary apparatus of the eye: assessment of changes in the tissues of the ocular surface and eyelids - I. A. Filatova; S. A. Shemetov; Yu. P. Kondratieva (Российский офтальмологический журнал, 2022)
Purpose: to evaluate the effectiveness and safety of combination therapy using the moisturizing ophthalmic solution, Hyloparin-Comod®, and the lubricating ophthalmic agent Parin-Pos® in complex medical management in the early stages after reconstructive interventions on the auxiliary apparatus of the eye.Material and methods. The clinical group consisted of 30 patients (40 eyes) aged 18 to 75 (m = 58.46 ± 7.31), of which 7 (23.3 %) were men; and 23 (74.7 %) women. Of these, 18 patients had ptosis of the upper eyelid (of which 10 had bilateral ptosis), 8 had inversion of the eyelids and 4 had eversion. All patients underwent reconstructive plastic surgery on the auxiliary apparatus of the eye: ptosis of the upper eyelid was treated by various methods depending on its type: 18 patients received plastic surgery of the levator aponeurosis (in 8 cases on both eyes; simultaneously, blepharochalasis resection was performed), 4 patients underwent levator shortening, 4 patients underwent eyebrow suspension (of these, 2 patients had the procedure on both eyes, hanging to the eyebrow – 4 operations (both eyes were operated on in two patients), 2 had tarzomyectomy; 8 had elimination of inversion, and 4 had elimination of eversion. In the postoperative period, instillations of antiseptics and antibiotics were supplemented by tear replacement and keratoprotective therapy: Hyloparin-Comod® was instilled 3 times during the day, while Parin-Pos® ointment was placed under and on the eyelids before going to bed. The course of treatment lasted 1 month. All patients underwent a standard ophthalmological examination before surgery as well as 2 weeks, 1 month and 3 months after surgery. The criteria for evaluating the effectiveness of treatment were the condition of the eyelid skin on a pointwise scale (Manchester scar scale), the result of biomicroscopy / biomicroscopy with fluorescein staining of the conjunctiva and cornea, Norn test.Results. In all cases of the use of Hyloparin-Comod® and Parin-Pos® combination, good subjective tolerability was noted, the patients had no complaints of discomfort due to the use of drops or ointment.Conclusion. The results obtained demonstrate that the proposed combination of drugs contributes to improving the favorable condition of eyelid skin and wound healing with the formation of a delicate scar, rapid resolution of conjunctival and eyelid swelling, prevention of corneal microerosions, minimization of corneal epithelial edema and tear film stability.